Integrative analysis of mRNA and microRNA expression profiles in laryngeal squamous cell carcinoma. Issue 3 (26th October 2018) - Ekmekci, Cumhur Gokhan; Coskunpinar, Ender; Avci, Hakan; Farooqi, Ammad Ahmad; Orhan, Kadir Serkan; Akbas, Fahri
Abstract: Larynx cancer is a therapeutically challenging disease. Rapidly evolving experimentally validated data have significantly improved our understanding of the complex role of numerous RNA, DNA, and proteins that play a role in the development and progression of cancer. Based on the insights from approximately two decades of research, it seems clear that microRNAs (miRNAs) have revolutionized our concepts related to the main role of noncoding RNAs in different cancers' progression, development, and metastasis. Mechanistically, miRNAs have been reported to regulate different RNAs and finally protein‐coding genes. The expression profiling of miRNAs and messenger RNA (mRNAs) was conducted for a deeper analysis of the miRNAs and mRNAs which play an essential role in larynx cancer. Downregulation or upregulation over twofolds in the miRNAs was considered to be significant, and that of sixfolds or below was considered to be significant for the mRNAs. In accordance with this approach, the expression levels of 43 miRNAs were increased in this study, whereas the expression levels of 129 were decreased. Accordingly, all the genomic expression studies provided evidence of upregulation of 97 genes, whereas 128 genes were found to be downregulated. Among these miRNAs, hsa‐miR‐20a‐3p and hsa‐miR‐1972 were noted to be important in the etiology of larynx cancer.